Near diffraction-limited performance of an OPA pumped acetylene-filled hollow-core fiber laser in the mid-IR - Dadashzadeh, Neda; Thirugnanasambandam, Manasadevi P.; Weerasinghe, H. W. Kushan; Debord, Benoit; Chafer, Matthieu; Gerome, Frederic; Benabid, Fetah; Washburn, Brian R.; Corwin, Kristan L. (My University, 2017)
We investigate the mid-IR laser beam characteristics from an acetylene-filled hollow-core optical fiber gas laser (HOFGLAS) system. The laser exhibits near-diffraction limited beam quality in the 3 μm region with M2 = 1.15 ± 0.02 measured at high pulse energy, and the highest mid-IR pulse energy from a HOFGLAS system of 1.4 μJ is reported. Furthermore, the effects of output saturation with pump pulse energy are reduced through the use of longer fibers with low loss. Finally, the slope efficiency is shown to be nearly independent of gas pressure over a wide range, which is encouraging for further output power increase.
Keywords: Fiber lasers; Gas lasers; Hollow core fibers; Laser beam characterization